2018
DOI: 10.1002/lary.27251
|View full text |Cite
|
Sign up to set email alerts
|

A standardized, closed‐loop system for monitoring pediatric tracheostomy‐related adverse events

Abstract: 4. Laryngoscope, 128:2419-2424, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Standardized monitoring and reporting of tracheostomy‐related airway complications are challenging within hospital systems 23 and even more limited in outpatient settings. A multicenter observational study of TDC in Spain found 50% of patients with a tracheostomy‐related death died at home from severe obstruction of the cannula and failure of resuscitation measures 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Standardized monitoring and reporting of tracheostomy‐related airway complications are challenging within hospital systems 23 and even more limited in outpatient settings. A multicenter observational study of TDC in Spain found 50% of patients with a tracheostomy‐related death died at home from severe obstruction of the cannula and failure of resuscitation measures 24 .…”
Section: Discussionmentioning
confidence: 99%
“…More than half are less than a year old when the tracheostomy is placed. The need for long-term mechanical ventilation in infants and children often stems from respiratory problems associated with prematurity, hypotonia, bronchopulmonary dysplasia, neurological impairment, and congenital heart and lung disease (Liu et al, 2014;McKeon et al, 2018;Sakai et al, 2019;Watters, 2017). The large set of skills that lay caregivers must acquire to care for the child at home is daunting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…HMV through a tracheostomy requires a complex set of skills that need to be mastered by caregivers. Children requiring a tracheostomy often have multiple chronic and complex comorbid conditions (Liu et al, 2014;McKeon et al, 2018). Sterni et al (2016) suggested that among children in the United States with special healthcare needs, few have more challenges than those requiring chronic home invasive ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…All TRAEs were standardized per 1000 inpatient tracheostomy-days, which was calculated automatically by a hospital-generated list each month. 4 The standardized frequency of events was maintained in a running chart to track trends. The TRAEs were also categorized by event type to emphasize the most commonly occurring events and highlight areas for improvement.…”
Section: Standardized Trae Reporting Systemmentioning
confidence: 99%
“…Multidisciplinary coordinated care has been shown to effectively reduce the occurrence of adverse events in patients with a tracheostomy. 4 The following 5 key drivers of tracheostomy care have been established to help implement quality-driven care: standardization of care, broad staff education, patient and family involvement, monitoring of outcomes, and multidisciplinary collaboration. 5 In 2015, Boston Children's Hospital (BCH), Boston, Massachusetts, created a multidisciplinary tracheostomy team (MDT) to implement these key drivers.…”
mentioning
confidence: 99%